Effect of 25-hydroxycholecalciferol and high phytase doses on performance, vitamin D status, bone mineralization, and mechanistic target of rapamycin gene expression of broilers - L.S. Bassi; C.C.S. Martins; C.A. Lozano-Poveda; I.C. Dias; S.G. Oliveira; A. Maiorka (Animal)
The use of exogenous phytase and vitamin D3 metabolites such as 25-hydroxycholecalciferol (25-OH-D3) for poultry is well consolidated, but the potential for additive effects when supplementing both requires further investigation. This study investigated possible interactions between supplementation of 25-OH-D3 and high doses of phytase for broilers fed Ca− and P-deficient diets. A total of 1 200 one-d-old male broiler chicks were randomly allocated from one of four dietary treatments in a 2 × 2 factorial arrangement: 600 or 2 000 phytase units (FYT)/kg and with or without the inclusion of 25-OH-D3 at 69 µg/kg, with 12 replicates of 25 broilers each. Two feeding phases were stablished (1-to-21 and 22-to-42 d) and all diets contained commercial levels of vitamin D3 (100 µg/kg) with total Ca and available P respectively set to 0.6 and 0.3%. Supplementation with 25-OH-D3 increased body weight gain (BWG) and reduced feed conversion ratio (FCR) from 1 to 21 d (P < 0.05), as well as increased BWG from 1 to 42 d (P < 0.05). Serum 25-OH-D3 levels at 21 and 42 d were increased with 25-OH-D3 (P < 0.001). Phytase did not affect growth performance from 1 to 21 d, but a higher dose (2 000 FYT/kg) reduced feed intake and FCR from 22 to 42 d compared to 600 FYT/kg, also reducing FCR in the total period (P < 0.05). The mRNA expression of mechanistic target of rapamycin in breast muscle assessed at 42 d was enhanced with 2 000 FYT/kg (P < 0.001). Bone weight, bone contents of ash, Ca, and P, and bone breaking strength of tibia bone measured at 42 d were not affected by any dietary treatment. Although both additives are known to improve dietary Ca and P utilization, there were no detected additive or synergic effects. The results suggested that the inclusion of 25-OH-D3 and phytase combined with regular vitamin D3 levels can help minimize losses of performance and bone mineralization of broilers fed Ca- and P-deficient diets. Furthermore, vitamin D status is refined with dietary 25-OH-D3 and potential improvements on breast meat yield can be obtained with a high phytase dose of 2 000 FYT/kg.